A robust passivity based model predictive control for buck converter suppling constant power load. (November 2021) - Zhou, Jiyao; Zhang, Qianye; Hassan, Mustafa Alrayah; Zhang, Zehua; Hou, Mingxuan; Wu, Shang; Li, Yongjian; Li, Erping; Guerrero, Josep M.
Abstract: In this paper, the instability problem caused by the constant power load in Buck converter is addressed. In order to solve this instability problem, a composite controller is proposed. Due to the double loop structure of this controller, the passivity based control (PBC) is adopted in the voltage loop to track the reference voltage and make the system stable, while a simplified continuous control set model predictive control (CCS-MPC) is selected as the current controller to track the current reference. Moreover, in order to improve the robustness of the controller and avoid the static error in output, a high order disturbance observer (HODO) is designed out to compensate the negative effects caused by the disturbance and uncertainty. Then, a mixed potential theory based large signal stability analysis is conducted to investigate the large signal stability of the studied system. In order to verify the proposed method, MATLAB simulation, OPAL-RT based hardware in loop and rapid control prototype experiments are conducted.